Application of Genetically Modified Organisms in Waste Management – A Review - Ebah, EE; Yange, IA; Ohie, IR; Inya, OJ (Stamford Journal of Microbiology, 2022)
Mankind has suffered many deleterious consequences from improper waste management following the advent of industrialization and xenobiotic wastes. Although there are several methods for treating waste such as physical methods which includes; reuse, recycling and landfills of waste, but the use of biological agents is preferred. Genetically Modified Organisms (GMOs) are microbes employed for enhanced degradation strategy which has greater prospects over the wild microbes. These bacteria can persist and transfer the genes to other microbes resulting in unintended effects in microbial community. The development of bioluminescent suicidal GMOs could be a way out. This review advocates for more research into this important area in order to tackle the perennial problems of waste management. Stamford Journal of Microbiology, Vol.12 (1) 2022: 15-20